Monitoramento Costeiro das Praias de São Bento do Norte e Caiçara do Norte - NE/Brasil - TABOSA, WERNER FARKATT; LIMA, ZULEIDE; VITAL, HELENICE; GUEDES, INGRED MARIA GUIMARÃES (Pesquisas em Geociências, 2001)
Sedimentary dynamic studies were conducted on the North littoral of Rio Grande do Norte State, comprising the São Bento do Norte and Caiçara do Norte cities, based on coastal processes data (wind, currents, waves and tides), beach profiles (monitoring six beach profiles, between June of 2000 and august of 2001), and elements in the morphologic and structural features. The coastline changes due to erosion and deposition are the major concern for the coastal zone management of this area. This work is setting the necessity to understand the causes of erosion before construction of protective structure on erosional beaches. Some items can be observed: 1) The destruction effects in the coastline were not eliminated by the construction of a groyne-field; 2) The increase of the erosion process in the area after the last groyn. The main modifications happened on the months of November 2000 and March 2001, probably conditioned mainly by the change of the medium direction of the winds, that varied from 225ºAz to 320ºAz in this period of 14 months of monitoring. In the month of November 2000, the registered average was of the order of 72ºAz (profile P1) and 90ºAz (profile P6), in the same sequence we obtained a variation of the order of 95ºAz and 85ºAz, for the month of March of 2001. In this context, it was observed that the period of repetition of the waves reached averages of the order of 2’03”Seg (mar/01, profile P1) and 6’07”Seg (mar/01, profile P6). The height of the waves was also registered in this period as being the highest, with values of 0,44m (mar/01, profile P1) and 0,50m (mar/01, profile P6). The beaches in the studied area can be classified as reflective to intermediate.